Specific sound frequency improves intrinsic water efficiency in rice leaf by imparting changes in stomatal dimensions - Jusoh, Mashitah; Ramlee, Shairul Izan; Pydi, Faiznur Iffah; Mazlan, Nur Aishah; Berahim, Zulkarami; Muhamad Mujab, Azzami Adam; Sinniah, Uma Rani; Yeoh, Joanne Pei Sze; Khalid, Khalisanni; Yaapar, Muhammad Nazmin (Universiti Putra Malaysia Press, 2022)
Various attempts have been made to increase rice production, including breeding for high-yielding and stress-tolerant varieties, a good crop management system, and increased agricultural input in rice production. Soundwave stimulation has been demonstrated to affect plant growth; thus, this method can be employed in the current rice production methods to improve yield. The study aims to determine the effects of different sound wave qualities on the general growth, physiological, and morphological of rice seedlings. Rice seeds of the MR219 variety were grown under a glasshouse condition in a nested design with five replications and were stimulated with various sound wave frequencies. Various sound wave frequencies, 380, 359, 357, 353, and 350 Hz, were obtained by placing the pot at varying distances (80, 160, 240, 320, and 400 cm, respectively) from the sound source, except control treatment. There were significant effects in some of the parameters: plant height, leaf physiology, and stomatal pore and length when treated with varying sound wave qualities. Plants can be stimulated with 380, 357, and 350 Hz soundwaves frequencies for the best photosynthetic experience. In addition, 359 Hz of sound wave stimulation resulted in high water use efficiency, which is beneficial in improving crop performance in drought conditions. Thus, it was demonstrated that the sound wave stimulation method has the potential to enhance rice performance in addition to the regular agronomic practices of rice production in farmers’ fields.